PERBEDAAN HASIL BELAJAR SISWA YANG DIAJAR MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PROBLEM BASED LEARNING PADA MATERI PENCEMARAN DAN KERUSAKAN LIGKUNGAN DI KELASVII SMP NEGERI 1 SEI BINGAI KABUPATEN LANGKAT - Dwi Aryuli Sitepu; Masdiana Sinambela (Universitas Negeri Medan, 2017)
This study aims to determine the differences of student learning outcomes using Problem Based Learning Model with Model Project Based Learning on the material Pollution and Environmental Degradation in class VII SMP Negeri 1 Sei Bingai T.P 2015/2016 consists of 7 classes with 224 students enrolled. While samples taken by random sampling as much as two classes of 64 students; 32 students of class VII-1 (using Problem Based Learning Model Learning) and 32 classes VII-2 (using Project Based Learning Model). Type of research is experimental. In the experimental class I (using Problem Based Learning Model) obtained an average student learning outcomes at 82.71 with a standard deviation of 4.75, while the experimental class II (using the Model Learning Project Based Learning) has an average of 90.63 with a standard deviation of 5.32. The big difference in learning outcomes is proved by testing the hypothesis by using t-test at the level of α = 0.05, which were encountered (14.14)> t table (1.6697). Hypothesis test used t test showed that the result was significantly different at the level of confidence .Keywords: Hasil belajar siswa, Problem Based Learning, Project Based Learning.